Looted Libraries and Legitimation Policies: Ptolemy, the Library of al-Arawšī and the Translation Movement in Toledo - Bellver, José (Arabica, 2021)
MS Tunis, Dār al-kutub al-waṭaniyya, 7116, is the only extant manuscript containing a complete copy of the Isḥāq/Ṯābit version of the Almagest. Paul Kunitzsch has underlined the close similarities between the marginal notes in the Tunis manuscript and those in Gerard of Cremona’s Latin translation of the Almagest, so that Kunitzsch has concluded that Gerard of Cremona had a manuscript close to the Tunis manuscript before him during the revision of his translation of the Almagest. A note in MS Tunis, Dār al-kutub al-waṭaniyya, 7116, points out that this manuscript was copied from a model owned by al-Arawšī, a bibliophile living in Valencia famous for the size of his library, a significant part of which was looted by al-Maʾmūn b. Ḏī l-Nūn and sent to Toledo, arguably shortly before Ṣāʿid al-Andalusī wrote his Ṭabaqāt al-umam. Based on MS Tunis, Dār al-kutub al-waṭaniyya, 7116, the present contribution explores the significance of al-Arawšī’s looted library as an important link between Umayyad Cordoba and Toledo. It also calls attention to the highly unusual paper of MS Tunis, Dār al-kutub al-waṭaniyya, 7116, made of woven fibers, maybe flax.